Effects of a coal phase-out in Europe on reaching the UN Sustainable Development Goals - S. Vögele; K. Govorukha; P. Mayer; I. Rhoden; D. Rübbelke; W. Kuckshinrichs (Environment, Development and Sustainability, 2022)
Several European countries plan to phase out coal-fired power plants in order to reach their greenhouse gas abatement targets. Additionally, the phase-out will bring about so-called ancillary effects or co-effects. In our study, we focus on the co-effects induced in the countries that export coal to Europe. Furthermore, we examine the ancillary effects imposed on China as a major supplier of technologies (like solar energy technologies) that will replace coal-fired power plants. Using a combination of an input-output model, econometric analysis and employing the concept of the United Nations' Sustainable Development Goals, we assess impacts of coal phase-out policies on environmental, economic, and societal dimensions. Our results show that despite negative impacts on income and employment in coal-exporting countries, a phase-out of coal-fired power plants is linked with multiple positive effects. In particular, we observe improvements in water management and biodiversity conservation, reduced release of pollutants, and improvements on a societal level. However, even if we consider a reduction in the use of coal in the European steel production sector as an additional challenge, these positive impacts on coal exporting countries remain rather small. The same applies to the effects we observe for China.
Keywords: 330; Phase-out; Coal; Sustainable Development Goals; Input-output analysis; Coal-exporting countries